Analisis Holder C-Hook dengan Metode Elemen Hingga - Abi Rafdi Haidi; Budianto Budianto; Widya Emilia Primaningtyas (Proceedings Conference On Design Manufacture Engineering And Its Application, 2021)
This study, an analysis of the construction of the c-hook holder will be carried out with ASTM A36 material, to determine the strength of the c-hook holder structure. The analysis process uses the FEM (Finite Element Methods) approach using FEM-based software. The validity of the simulation results is carried out on the value of the results of the von misses stress and deflection. Validation of the simulation results is done by manual calculations. From the results of the analysis, it is known that the stress that occurs at a predetermined load using ASTM A36 material is 180 MPa. The results of the analysis of the deflection that occurs in ASTM A36 material is 0.39 mm. From the results of the safety factor analysis, the safety factor value was 1.3. From the results of the analysis, the stress, deflection, and safety factor using the material are still below the predetermined limits, so that the c-hook holder construction can be said to be safe. Based on the results of the design and analysis that has been done, it can be concluded that the c-hook holder with ASTM A36 material can be used and has high security.